2000
DOI: 10.3141/1728-06
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Fracture Testing of Asphalt Binders: Regular and Modified Systems

Abstract: The results of low-temperature fracture testing of a large number of both regular and modified asphalt binders are discussed. Two Strategic Highway Research Program (SHRP) binders (Materials Reference Library Codes AAG-2 and AAN) were evaluated with 5 percent by weight of a variety of commonly used polymer modifiers. Specimens of three different sizes were tested in a three-point bend configuration, both with and without a notch. The original SHRP effort was aware of the need for a rigorous fracture mechanics-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 4 publications
2
41
1
1
Order By: Relevance
“…This approach has been applied to explore the mechanism of fracture in asphalt mixtures as early as in 1960s [6] and has become increasingly popular in the research community after 1990s [7][8][9][10][11][12][13][14][15]. There are many methods of fracture testing in hot mix asphalt (HMA), including the Single-Edge Notched Beam [12,14,16,17], the Semi-Circular Bend (SCB) [13,18,19], the IDT fracture parameter [20,21], and the Disc-Shaped Compact Tension Test (DCT) [15,22,23]. All of these mixture fracture tests have advantages and disadvantages [15].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been applied to explore the mechanism of fracture in asphalt mixtures as early as in 1960s [6] and has become increasingly popular in the research community after 1990s [7][8][9][10][11][12][13][14][15]. There are many methods of fracture testing in hot mix asphalt (HMA), including the Single-Edge Notched Beam [12,14,16,17], the Semi-Circular Bend (SCB) [13,18,19], the IDT fracture parameter [20,21], and the Disc-Shaped Compact Tension Test (DCT) [15,22,23]. All of these mixture fracture tests have advantages and disadvantages [15].…”
Section: Introductionmentioning
confidence: 99%
“…introduced the force ductility test, followed by a high number of researchers that utilized this method to evaluate the tensile properties of asphalt [29][30][31]. The results [7,8,31,32] reported that the force extension test was a reliable and effective method.…”
Section: Force Ductility Test In 1976 Anderson and Wileymentioning
confidence: 99%
“…These are: (i) single-edge notched beam, SE(B), specimen [2,15,16]; (ii) disc-shaped compact tension, DC(T), specimen [17][18][19]; (iii) semi-circular bending, SCB, specimen [11,[20][21][22][23]; and (iv) double-edged notched tension, DENT, specimen [12]. Among the various options, SCB testing was selected in this study because it has several benefits compared to other fracture test methods.…”
Section: Scb Tests For Fracture Propertiesmentioning
confidence: 99%